2016
DOI: 10.7737/jkorms.2016.41.3.023
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Weapon Target Assignment Problem under Uncertainty in Targeting Accuracy

Abstract: We consider a model that minimizes the total cost incurred by assigning available weapons to existing targets in order to reduce enemy threats, which is called the weapon target assignment problem (WTAP). This study addresses the stochastic versions of WTAP, in which data, such as the probability of destroying a target, are given randomly (i.e., data are identified with certain probability distributions). For each type of random data or parameter, we provide a stochastic optimization model on the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Furthermore, studies on the solution methodologies for a WTA have been actively performed because Lloyd and Witsenhausen [19] proved that it is a combinatorial optimization problem and is NP-Complete. Some researches, such as those of Chang et al [20], Orlin [21], and Lee and Shin [22], suggested exact solution methods under the assumption of one type of weapon or less than one bomb per target. Kwon et al [23] linearized the WTA model by the logarithmic transformation and proposed the Lagrangian relaxation approach and branch-andbound (B&B) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on the solution methodologies for a WTA have been actively performed because Lloyd and Witsenhausen [19] proved that it is a combinatorial optimization problem and is NP-Complete. Some researches, such as those of Chang et al [20], Orlin [21], and Lee and Shin [22], suggested exact solution methods under the assumption of one type of weapon or less than one bomb per target. Kwon et al [23] linearized the WTA model by the logarithmic transformation and proposed the Lagrangian relaxation approach and branch-andbound (B&B) algorithm.…”
Section: Introductionmentioning
confidence: 99%